Deans and Truants : Race and Realism in African American Literature - Jarrett, Gene Andrew, 1975- (Book collections on Project MUSE., 2007)
For a work to be considered African American literature, does it need to focus on African American characters? Or is it enough for the author to be identified as African American? Jarrett traces the shifting definitions of African American literature and the authors who wrote beyond those boundaries at the cost of critical dismissal or obscurity.